The ’separate performative’ account of the German right dislocation - Averintseva-Klisch, Maria (ZAS Papers in Linguistics, 2006)
In my paper, I show that the so-called German right dislocation actually comprises two distinct constructions, which I label 'right dislocation proper' and 'afterthought'. These differ in their prosodic and syntactic properties, as well as in their discourse functions. The paper is primarily concerned with the right dislocation proper (RD). I present a semantic analysis of RD based on the 'separate performative' account of Potts (2004, 2005) and Portner (forthc.). This analysis allows a description of the semantic contribution of RD to its host sentence, as well as explaining certain semantic constraints on the kind of NP in the RD construction.